Kajian Papan Iklan “Miras” pada Ruang Publik Terbuka di Kota Denpasar - Sutarwiyasa, I Ketut; Setiawan, I Ketut; Thalib, Emmy Febriani (Jurnal Bahasa Rupa, 2024)
This study examines the experiences and perceptions of Denpasar residents regarding alcohol advertisements in public spaces. In a society that upholds religious and cultural values, the presence of such advertisements sparks controversy due to concerns about their impact on social norms and morality. Using Maurice Merleau-Ponty's theory of the phenomenology of perception, this research aims to analyze how alcohol advertisements influence public perception based on the interaction between the body, consciousness, and social environment. The method employed is a phenomenological approach with in-depth interviews and observations of advertisements in public spaces. The findings reveal that perceptions vary significantly depending on age, gender, occupation, and religious background. The majority of respondents from Muslim and Hindu religious groups reject the presence of these advertisements, considering them to be in conflict with religious values and expressing concern about their potential influence on younger generations. On the other hand, younger respondents tend to be more permissive, as long as the advertisements do not disrupt social order. This study has not yet explored in depth how differences in the context of public spaces, such as tourist areas and local environments, influence public perceptions of alcohol advertisements.